Lactobacillus rhamnosus ameliorates acne vulgaris in SD rats via changes in gut microbiota and associated tryptophan metabolism - Huang, Yukun; Huang, Yaxin; Xia, Dengmei; Liu, Lu; Xiong, Xia; Ouyang, Yongliang; Deng, Yongqiong (Frontiers in Immunology, 2024)
The depletion of beneficial bacteria in the gut has been found in patients with acne vulgaris and the supplement of Lactobacillus rhamnosus (L. rhamnosus) could lead to the improvement of adult acne in previous studies. Nevertheless, the potential mechanism of L. rhamnosus in the amelioration of acne vulgaris has not been elucidated yet. Methods: To mimic the human intestinal environment, a pseudo-germ-free rat model was used, and then gut microbiota from healthy individuals and acne patients were transplanted into rats. The effect of L. rhamnosus and tryptophan (Trp) metabolites on rat acne model were investigated by gavage. The 16sRNA analysis and targeted measurement of metabolites were performed to discover the differences of gut microbiota and metabolites between groups. Then HaCaT cells pretreated with Cutibacterium acnes (C. acnes) were employed to validate the effect and mechanism of Trp metabolites on acne. Results: L. rhamnosus significantly improved acne-like symptoms in rats by suppressing the level of inflammatory cytokines such as IL-1β, IL-6, and TNF-α. L. rhamnosus induced an increase in the production of Indoleacetic acid (IAA) and indole via targeted Trp metabolic analyses. Furthermore, L. rhamnosus promoted the bacteria diversity and also enhanced the Firmicutes/Bacteroidota (F/B) ratio which was positively related both with IAA and indole. Finally, the roles of IAA and indole in alleviating the inflammation of acne vulgaris were confirmed in both vitro and vivo, which could be reversed by AhR inhibitors. Conclusion: Our study demonstrated that L. rhamnosus could exert its therapeutic effects on acne vulgaris by modulating the gut microbiota and regulating associated Trp metabolites.